An assessment of gait spatiotemporal and ground reaction force characteristics of patients with Parkinson compared with normal elderly - Keyvan Sharifmoradi; Nader Farahpour; Abbas Bahram; Mohammad Taghi Karimi; Mehrdokht , Mazdeh (Vesnu Publications, 2014)
Introduction: Parkinson disease (PD) is associated with abnormalities in movements, including in gait. Yet, there is lack of information about kinetic aspects of gait in PD. The objectives of this study were to evaluate the temporal variables and ground reaction forces during gait in PD patients and control group. Materials and Methods: twelve patients with PD and 15 normal elderly subjects of between 50-75 years of age participated in this study. A Vicon motion analysis system with four cameras and as well as two Kistler force plates were used to measure the temporal variables and ground reaction forces (GRF) during the gait. For statistical analysis independent student-t test was used. The type one error was set at α<0.05. Results: Walking speed, stride length, second pick of vertical ground reaction force, and posterior-anterior (propulsive) forces in patients were significantly smaller than that of in normal subjects (p <0.05). The double support time in PD patients was increased compared to normal subjects (p>0.05). GRF in both groups were symmetrical. Conclusion: Reduced walking speed, increased double support time in PD patients could be due to a neuromuscular adaptation to compensate balance deficit. The second peak of the vertical GRF and the propulsive force (posterior-anterior) GRF are related and the decreased GRF in PD might be due to the reduction of the walking speed. However, this pattern may result in a muscle weakness in long term.  Key words: Parkinson's Disease, gait, kinetics